2022
DOI: 10.3390/bs12060199
|View full text |Cite
|
Sign up to set email alerts
|

The “Ifs” and “Hows” of the Role of Music on the Implementation of Emotional Regulation Strategies

Abstract: Music is believed to aid the implementation of emotion regulation strategies like distraction or reappraisal, but empirical studies have shown null results. However, the moderating role of one’s relation with music (musical sophistication) and/or executive functioning skills has not been considered yet. In addition, little is known about how music acts. In the present study, we induced anger in a group of participants characterized by musical sophistication and executive functioning. We asked them to regulate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 56 publications
(78 reference statements)
0
5
0
1
Order By: Relevance
“…When participants perform cognitive reappraisal tasks, they may consider the background music irrelevant; therefore, they will not incorporate the influence of happy music into the emotional regulation process. Carvalho found that for people who enjoy music, a combination of music and cognitive reappraisal can improve emotion regulation [ 9 ]. Most importantly, the effect of happy music on cognitive reappraisal was influenced by individual differences.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When participants perform cognitive reappraisal tasks, they may consider the background music irrelevant; therefore, they will not incorporate the influence of happy music into the emotional regulation process. Carvalho found that for people who enjoy music, a combination of music and cognitive reappraisal can improve emotion regulation [ 9 ]. Most importantly, the effect of happy music on cognitive reappraisal was influenced by individual differences.…”
Section: Discussionmentioning
confidence: 99%
“…Baltazar et al showed that the combination of music and cognitive reappraisal did not significantly improve the effect of emotion regulation compared with music or emotion regulation alone [ 8 ]. Carvalho experimentally demonstrated that, in people who enjoy music, the combination of music and cognitive reappraisal improved emotion regulation [ 9 ]. They also found that in cognitive reappraisal, the musical features to which participants focused their attention were not the lyrics of the song, but the feelings and memories triggered by the music, which may increase empathy and facilitate the re-perception of events [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This means that, despite its self-reported nature, the instrument allows a quantification of individual levels of performance (Lima et al, 2020). The publication of the English version of the Gold-MSI obtained a vast resonance and the use of the instrument in diverse research areas pertaining to music psychology has contributed to add knowledge about the concept of musical sophistication and how it relates to various human functions and systems such as emotion regulation (Carvalho et al, 2022), language perception (Lad et al, 2021;Yates et al, 2018), music-induced emotions and affects perception (Küssner & Eerola, 2019;Smit et al, 2019;Taruffi et al, 2017) and age-related changes in brain structure (Chaddock-Heyman et al, 2021).…”
Section: Sophistication Indexmentioning
confidence: 99%
“…Asimismo, la música es una fuente de placer que se torna en un estímulo altamente motivador y gratificante que genera fuertes recompensas en el ser humano (Zald & Zatorre, 2011). De hecho, la música comúnmente se relaciona positivamente con mayores índices de bienestar , siendo un estímulo frecuentemente empleado por las personas para su propia autorregulación emocional (Carvalho et al, 2022;Fernández-Company & García-Rodríguez, 2021). Sobre este particular, la falta de estrategias de regulación emocional se encuentra asociada a conductas desadaptativas (Navarro-Loli et al, 2020).…”
Section: Introductionunclassified